Diversity in the Australian speech-language pathology workforce: Addressing Sustainable Development Goals 3, 4, 8, and 10. - Nancarrow, Susan; McGill, Nicole; Baldac, Stacey; Lewis, Tara; Moran, Anna; Harris, Nichola; Johnson, Trish; Mulcair, Gail (International Journal of Speech-Language Pathology, 2023)
Individuals have multiple intersecting identities, unique perspectives, and experiences which provide opportunities for new ways to interact, support inclusion and equity, and address the Sustainable Development Goals (SDGs). This commentary explores the diversity of the speech-language pathology workforce in Australia. A survey of Australian speech-language pathologists (SLPs; n = 1,638) distributed in November and December 2021 explored personal characteristics and experiences of the workforce. Almost 30% of SLPs who responded reported having experiences or perspectives that were relevant to service users and a quarter described other lived experiences, which included disability, cultural and linguistic background, mental health, caring responsibilities, neurodiversity, and being LGBTQI+. This commentary affirms the value of diversity among allied health professions to enrich practice with individuals and communities. By understanding the diversity of the speech-language pathology workforce and perspectives of historically marginalised or invisible groups, the profession can introduce strategies to more meaningfully engage and support people with diverse backgrounds and perspectives in the workforce and enhance service equity and accessibility for people with communication and swallowing disabilities. This commentary focusses on SDG 3, SDG 4, SDG 8, SDG 10.